Morning stiffness response with delayed-release prednisone after ineffective course of immediate-release prednisone. (3rd September 2015) - Alten, R; Holt, R; Grahn, A; Rice, P; Kent, J; Buttgereit, F; Gibofsky, A
Abstract : Objective : To assess morning stiffness in rheumatoid arthritis (RA) patients switched from immediate-release (IR) to delayed-release (DR) prednisone. Method : Circadian Administration of Prednisone in Rheumatoid Arthritis-1 (CAPRA-1) is a 12-week, randomized, multicentre, active-controlled study of morning stiffness that consisted of a double-blind phase and a 9-month open-label extension. Patients receiving IR prednisone with no significant improvement after the double-blind study were switched to DR prednisone. Morning stiffness duration and median absolute and relative changes in pain and global assessment were evaluated (3, 6, and 9 months). Results : In patients switched from IR to DR prednisone (n = 110), statistically significant reductions in morning stiffness occurred over 3 months and were sustained for 9 months. Absolute reduction of morning stiffness was ~50 min with > 40% relative reduction at each visit. Interleukin (IL)-6 levels were reduced by the same amount. Statistically significant and clinically meaningful mean reductions in morning stiffness were maintained at > 67 min at each visit along with significant improvements in pain and patient global assessment. There was no evidence of tachyphylaxis seen over the 9-month study. Conclusions : Patients receiving disease-modifying anti-rheumatic drugs (DMARDs) and IR prednisone who had not had significant reductions in morning stiffness demonstrated statistically significant and clinically meaningful improvements when switched to DR prednisone.